IMPLEMENTASI METODE HARGA POKOK PROSES DALAM PERHITUNGAN HARGA POKOK PRODUKSI PADA USAHA BATIK - Tri Irawati; Saiful Arifin (STMIK Sinar Nusantara, 2020)
The Batik is a company which produces apparel from the raw materials until the finished goods. It is called production. By the production, the company aims to produce high quality products with proper list price. Finally, the company will be able to compete with other companies. The purpose of this Last Project is to produce the application of The Computerization of Accounting System for Cost of Goods Manufacture with cost method process determine the list price so it can assist the disposal section in accounting process. The method used in this research was collecting the data including observation method, interview method, and literature technique. The process in making the application of The Computerization of Accounting System for Cost of Goods Manufacture with cost method process on Nur Hasida Batik in Sragen used a computer with Visual Basic 6 program, MySQL, and crystal report. The result of this Last Project Report is The Computerization of Accounting System for Cost of Goods Manufacture based on Orders which includes: goods data input, raw materials data input, labors costs data input, factory overhead data input, the transaction cost of goods, the transaction of the accounting for cost of goods manufacture and list price. It is also included the report of commodities’ data, the report of labors costs data, the report of commodities data, the report of factory overhead data, the report of the accounting for cost of goods manufacture and list price. Keywords: Raw material, labor cost, overhead, cost of goods manufacture